Field reports by Eugene Armstrong - Armstrong, Eugeneet al (1983)
An annotated list of birds sighted by Eugene Armstrong and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1983. Epson - sheet feed/flatbed